Accounting aspects of ocean iron fertilization - Wilfried Rickels; Katrin Rehdanz; Andreas Oschlies (Kiel Institute for the World Economy (IfW), 2009)
Diminishing emission budgets and increasing risks of catastrophic damages from climate change require analyses of rapid response options including geoengineering options such as ocean iron fertilization (OIF). To decide whether or not OIF might be such an option an assessment of its potential as an abatement option as well as its possible side effects is required. To explore the potential of OIF knowledge on the change of carbon stocks over time is needed. However, economic aspects including accounting of carbon credits need to be considered as well. In our analysis we use data from OIF modeling experiments for different years and analyze how many carbon credits would be generated and could be used for compliance. The amount of credit varies with the accounting method applied. Applying an accounting method which measures the net effect of OIF for the duration of 100 years leads to an annual carbon uptake of 0.56 to 1.69 GtC. For a shorter fertilization period, e.g. ten years the upper range increases to 2.57 GtC per year. Offsets due to other GHGs, especially N2O, as well as operational carbon emissions can be addressed by a discount factor. Considering all experiments and all accounting methods we find a maximum discount factor of 15 percent and an average value of 9 percent. From an economic as well as from an environmental perspective issuing temporary carbon credits which have to be replaced in the next commitment period seems most appropriate for short-term OIF and would provide the largest amount of credits at an early stage. This is equivalent to the existing tCER regulation under the Kyoto Protocol.
Keywords: Q51; Q54; Q56; 330; Climate change; ocean iron fertilization; permanence; carbon accounting; Klimaschutz; Meer; Düngemittel; Stahl; Kohlendioxid; Emissionsrechte; Welt